2016
DOI: 10.1093/jamia/ocw115
|View full text |Cite
|
Sign up to set email alerts
|

iCONCUR: informed consent for clinical data and bio-sample use for research

Abstract: Background: Implementation of patient preferences for use of electronic health records for research has been traditionally limited to identifiable data. Tiered e-consent for use of de-identified data has traditionally been deemed unnecessary or impractical for implementation in clinical settings.Methods: We developed a web-based tiered informed consent tool called informed consent for clinical data and bio-sample use for research (iCONCUR) that honors granular patient preferences for use of electronic health r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 26 publications
2
43
0
Order By: Relevance
“…According to research participants, access to their own health information is a key benefit of participation [ 46 ]. Research participants requested more transparency regarding the use of their data [ 38 , 58 ]. They expressed the right to control the sharing and use of their private health information [ 37 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to research participants, access to their own health information is a key benefit of participation [ 46 ]. Research participants requested more transparency regarding the use of their data [ 38 , 58 ]. They expressed the right to control the sharing and use of their private health information [ 37 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Research participants exposed to positive valence annotations indicated feeling less informed than participants receiving a combination of positive and negative valence annotations [ 30 ]. Various studies [ 15 , 37 , 58 , 62 ] provided insights into a personalized approach of an electronic informed consent platform. Research participants stated that they would like to receive personalized elements and tailored information such as the display of their name in the electronic informed consent form or the impact of their contribution on a specific research question [ 15 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, there are still concerns and barriers related to the tradeoffs between individual and institutional privacy and the societal benefits of sharing clinical data and to the practical challenges of harmonizing data across several institutions to build predictive models and decision support systems. [65][66][67][68][69][70]…”
Section: Measuring Performance and Redefining Metricsmentioning
confidence: 99%
“…Examples of EHR-integrated patient consent dashboards are demonstrating how patients can be active stewards of their own data, as well as controlling and managing consent and permissions. 60 Lastly, sharing with patients the clinical research results stemming from their involvement in EHR, face-to-face clinic visits that focus on engaging the patient in their care, and in-person contact with an individual who represents the research institution may all be ways of facilitating a culture of trust between patients and researchers.…”
Section: Building a Culture Of Trustmentioning
confidence: 99%